Description of Inpatient Satisfaction Levels for Nutrition Consultation Services at Regional General Hospitals - Retno Wahyu Ningsih; Yuli Laraeni; Joyeti Darni; Jaya Pandu RN; Tati Arisanti; Nurafiani Nurafiani (Poltekkes Kemenkes Mataram, 2023)
Background: Hospital nutrition services are an essential part of the entire service system for hospital patients. Nutrition consultation is a vital nutrition service because everyone has different problems. Quality nutrition consultation can also increase the effectiveness and efficiency of resources and provide patient satisfaction.Research Methods: This type of observational research with a cross-sectional design. The subjects used in the study were 34 patients in the inpatient room of Mataram City Hospital. The data collected in this study are all nutrition consulting services which include: the counselor's appearance, media, material, time, and place. The collected data is then processed by editing and coding manually, then tabulated from the answer scores obtained using a presentation table in the form of a diagram or table. Furthermore, the data were analyzed using descriptive analysis.Research Result: This study illustrates patient satisfaction with nutrition consultations conducted by nutritionists. The aspects assessed are reliability, responsiveness, assurance, attention, and evidence. Regarding reliability, the dominant value is satisfaction in nutrition officers providing services in a thorough and timely manner (64.71%). The responsiveness aspect illustrates the principal value of pleasure with being very satisfied with the nutrition officer who always takes the time to listen to patient complaints (55.88%). The aspect of guaranteeing the dominant value of the nutrition officer is acting politely and being friendly (61.8%). The attention aspect illustrates the principal value of nutrition officers willing to respond to patient complaints in a friendly manner regarding nutrition counseling provided with a delighted level (61.8%). In the aspect of the evidence, the dominant value of the nutrition officer item is the result of consultation with patients (leaflet/showing the effects of counseling) with a delighted level (58.8%).Conclusion: This study illustrates patient satisfaction with nutrition consultations conducted by nutritionists. The aspects assessed are reliability, responsiveness, assurance, attention, and evidence.